Serum calcium, albumin and tumor stage in cutaneous malignant melanoma. (October 2016) - Datta, Mridul; Savage, Paul; Lovato, James; Schwartz, Gary G
Aim: Assess the relationship of serum calcium and serum albumin to tumor stage and other clinical characteristics in patients with cutaneous malignant melanoma (MM).Patients & methods: A cross-sectional study to evaluate serum calcium as a marker of disease progression (n = 644) in MM.Results: Serum albumin was significantly lower among men (p < 0.01) and among patients with stage 4 disease (p < 0.05). In a multivariable regression model adjusted for age, gender and site, albumin-corrected calcium was positively associated with disease stage (odds ratio: 1.46; 95% CI: 1.02–2.07; p = 0.04). The odds of higher stage increased 60% for each 1.0 mg/dl increase in albumin-corrected calcium.Conclusion: Higher albumin-corrected serum calcium may be a marker of disease progression in MM.